2010
DOI: 10.1016/j.chemosphere.2010.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transfer of chlorinated contaminants in the leatherback turtles, Dermochelys coriacea, nesting in French Guiana

Abstract: a b s t r a c tWe examined the maternal transfer of organochlorine contaminants (OCs), pesticides (DDTS and HCHs) and polychlorinated biphenyls (PCBs), and the temporal variation of blood and eggs concentrations from 38 leatherback turtles (Dermochelys coriacea) nesting in French Guiana. PCBs were found to be the dominant OCs with respective mean concentrations of 55.14 ng g À1 lipid-mass for egg and 1.26 ng mL À1 wetmass for blood. OC concentrations were lower than concentrations measured in other marine turt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 48 publications
3
47
2
6
Order By: Relevance
“…Values for curved carapace length and width in foraging leatherbacks in this study were similar to those reported for nesting female leatherbacks in Costa Rica (Southwood et al, 1999(Southwood et al, , 2005, Gabon (Deem et al, 2006), Papua New Guinea (Benson et al, 2007c), Trinidad (Harms et al, 2007), and French Guiana (Guirlet et al, 2008). However, mean body weights of foraging female leatherbacks in California (512.466.82 kg; 380-607 kg; n513) were significantly higher than those previously reported in nesting adult female leatherbacks in Trinidad (287626 kg; 242-324 kg; n510) and Costa Rica (268644 kg; 196-308 kg; n56), where there was no overlap of ranges (Wallace et al, 2005;Harms et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Values for curved carapace length and width in foraging leatherbacks in this study were similar to those reported for nesting female leatherbacks in Costa Rica (Southwood et al, 1999(Southwood et al, , 2005, Gabon (Deem et al, 2006), Papua New Guinea (Benson et al, 2007c), Trinidad (Harms et al, 2007), and French Guiana (Guirlet et al, 2008). However, mean body weights of foraging female leatherbacks in California (512.466.82 kg; 380-607 kg; n513) were significantly higher than those previously reported in nesting adult female leatherbacks in Trinidad (287626 kg; 242-324 kg; n510) and Costa Rica (268644 kg; 196-308 kg; n56), where there was no overlap of ranges (Wallace et al, 2005;Harms et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, comparisons were not possible between foraging and nesting females from the same metapopulation or within the same ocean basin. Lead levels were not different between foraging (0.2060.08 ppm) and nesting female leatherbacks (0.1560.03 ppm) in this study, and they appear similar to nesting leatherbacks from French Guiana (0.1860.05 ppm; Guirlet et al, 2008) and slightly higher than levels measured in nesting leatherbacks in Gabon (0.08760.031 ppm; Deem et al 2006). Cadmium and lead might compete with essential metals for binding sites on metalloenzymes and both are carcinogenic and teratogenic; however, the toxicokinetics and threshold for toxic effects of metals in reptiles have not been determined (Linder and Grillitsch, 2000).…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations